Vaccination rates and determinants of nine recommended vaccines among migrants in China: a nationwide cross-sectional study. Issue 12 (2nd December 2021) - Wang, Jun; Zhu, Jingmin; Bai, Yang; Wang, Xueyao; Che, Yue; Liu, Jue
ABSTRACT: In the past 70 years, in order to strengthen disease prevention and improve people's health, China had introduced a series of vaccine policies. However, compared with the permanent population, studies on the vaccination situation of the migrants were lacking. This study aimed to evaluate the vaccination rates of nine recommended vaccines (HepB, HepA, FIn, DTaP, JE, Rab, MPSV, HF, and TIG vaccine) among migrants and related determinants. We used nationwide data from the 2017 Migrant Population Dynamic Monitoring Survey (MDMS) to analyze the vaccination rates of migrants in terms of gender, age, marital status, household registration, education, health level, etc. The total vaccination rate of nine recommended vaccines was 64.8% (6488/10013). Education level and health level were positively correlated with vaccination rates, but age was negatively correlated with vaccination rates. Migrants from urban regions had a higher vaccination rate than those from rural regions. Among the nine recommended vaccines, HepB vaccination rate was the highest (59.08%), while HF vaccination rate was the lowest (4.08%). Combined with policies and demographic characteristics, the relationship between age, household registration, health level, education level and vaccination were studied. The findings suggested that more attention should be given to vaccination of migrants, and the monitoring of vaccination of such groups should be strengthened through information technology.